ASUHAN KEPERAWATAN MASALAH PSIKOSOSIAL ANSIETAS PADA NY. R DENGAN PROLAPS UTERI DI KELURAHAN LIMO KOTA DEPOK - Safrida Azizah Iskandar, (2023)
Background: Uterine prolapse is the descent of the uterus into the vagina, with complete prolapse, the cervix protruding through the vagina, and the vagina being inverted. One of the treatment measures that can be taken for uterine prolapse is surgery. Individuals who will perform surgery tend to experience anxiety or anxiety. Anxiety is a feeling that arises in a person in the form of anxiety, worry, or discomfort as if something happened that is felt as a threat. This research was conducted to determine the extent to which clients know the methods to overcome the anxiety they feel and provide anxiety nursing care with uterine prolapse. Method: This research was conducted using the case study method. Research Result : In this case study found nursing problems, namely anxiety, for the actions taken, namely, deep breathing relaxation techniques, PMR techniques, and 5 finger hypnosis, in order to alleviate anxiety problems experienced by clients due to undergoing surgery. Conclusion : After being given nursing care to Mrs. R achieved the expected results, namely Mrs. R can control the feeling of anxiety that is felt by using the 3 methods that have been taught.